Number of cuts for estimating forage productivity in panicum maximum - Torres, Francisco Eduardo; Teodoro, Paulo Eduardo; Benites, Simone Botelho; de Oliveira, Elisa Fidêncio [UNESP]; Corrêa, Caio Cezar Guedes; da Silva, Flávia Alves (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2016)
The evaluation of the coefficient of repeatability (r) allows verify if the superiority or initial inferiority of an individual remains over the measurements, being important for genetic breading programs with forages. Thus, this research aimed to determine the minimum number of cuts for selection with greater efficiency and reliability and to phenotypic stabilization of P. maximum cultivars. The experiment was conducted during the months of September 2011 to October 2012 at the State University of Mato Grosso do Sul. It were used three P. maximum cultivars (Massai, Mombaça and Tanzânia) for evaluation of dry mass of leaves and stems and total dry mass in six cuts. From this cuts, it was estimated the coefficient of r repeatability by methods ANOVA, principal components (correlation and covariance matrices) and structural analysis, as well as the required number of cuts based on pre-established coefficients of determination (0.80, 0.85, 0.90, 0.95 and 0.99). Seven harvests are necessary to discriminate with 85% accuracy in P. maximum cultivars based on the traits dry mass of leaves, dry mass of stems and total dry mass. The exclusion of the first three harvests promotes increase in coefficients of repeatability and determination due to forage production stabilization of P. maximum cultivars.
Número de cortes para estimativa da produtividade de forragem em panicumm maximum
Keywords: Experimental precision; Reliability; Repeatability